Methamphetamine exposure drives cell cycle exit and aberrant differentiation in rat hippocampal-derived neurospheres - Wang, Shaomin; Wang, Liang; Bu, Qian; Wei, Qian; Jiang, Linhong; Dai, Yanping; Zhang, Ni; Kuang, Weihong; Zhao, Yinglan; Cen, Xiaobo (Frontiers in Pharmacology, 2023)
Methamphetamine (METH) abuse by pregnant drug addicts causes toxic effects on fetal neurodevelopment; however, the mechanism underlying such effect of METH is poorly understood.In the present study, we applied three-dimensional (3D) neurospheres derived from the embryonic rat hippocampal tissue to investigate the effect of METH on neurodevelopment. We found that METH treatment for 24 hours significantly and concentration-dependently reduced the size of neurospheres.Analyses of genome-wide transcriptomic profiles found that those down-regulated differentially expressed genes (DEGs) upon METH exposure were remarkably enriched in the cell cycle progression. By measuring the cell cycle and the expression of cell cycle-related checkpoint proteins, we found that METH exposure significantly elevated the percentage of G0/G1 phase and decreased the levels of the proteins involved in the G1/S transition, indicating G0/G1 cell cycle arrest. Furthermore, during the early neurodevelopment stage of neurospheres, METH caused aberrant cell differentiation both in the neurons and astrocytes, and attenuated migration ability of neurospheres accompanied by increased oxidative stress and apoptosis. Collectively, our findings reveal that 2 METH induces an aberrant cell cycle arrest and neuronal differentiation, which impairs the coordination of migration and differentiation of neurospheres.